Evaluation of methods for detection of asymptomatic individuals infected with Leishmania infantum in the state of Piauí, Brazil. - Gabriane Nascimento Porcino; Kátia Silene Sousa Carvalho; Débora Cavalcante Braz; Vladimir Costa Silva; Carlos Henrique Nery Costa; Isabel Kinney Ferreira de Miranda Santos (Public Library of Science (PLoS), 2019)
Background Visceral Leishmaniasis in humans presents with fever, anemia, and splenomegaly and can be lethal if not treated. Nevertheless, the majority of Leishmania infantum-infected individuals does not manifest symptoms and remain so provided they are not immunosuppressed. In this work, the performance of different tests was evaluated to detect asymptomatic individuals who were living in Teresina, Piauí state, Brazil, an endemic area for VL. Methodology L. infantum-specific antibodies were detected by ELISA and two different rapid immunochromatographic (IC) diagnostic tests, Kalazar Detect and OnSite, and parasitic loads were detected by real time PCR [qPCR]. Additionally, we measured levels of the biomarkers monokine induced by IFN-γ (MIG) and IFN-γ-induced protein 10 (IP-10) before and after stimulation of whole blood with soluble Leishmania antigen [SLA]. Principal findings Kalazar Detect and OnSite detected, respectively, 76% and 64% of patients presenting with active Visceral Leishmaniasis; 50% and 57% of patients remained positive in these tests, respectively, after treatment. Of the healthy participants in the study who were living in the endemic area, only 1.7% were positive with both of the IC tests. On the other hand, reactivity in ELISA tests revealed that 13% of these individuals presented asymptomatic infections; among VL patients, 84% presenting with active disease were reactive in ELISA, and after treatment, 55.5% were seropositive. L. infantum DNA was present in the blood of 37.9% of infected individuals living in the endemic area, while IP-10 and MIG biomarkers were detected in 26.7% of them. The greatest concordance of positivity occurred between ELISA and qPCR. Conclusion The association of different techniques can detect asymptomatic infections, however, more research is necessary to develop ideal biomarkers that are simple to use in the clinic and in field studies in areas endemic for Visceral Leishmaniasis.